INVESTIGATING ERRORS IN WRITING MECHANICS IN UNIVERSITY STUDENTSâ€™ ESSAYS - AISAH AYU SANDRAWATI; JURI JURIANTO JURIANTO (LINGUAMEDIA Journal, 2021)
Besides grammar, writing mechanics are one of important components for producing an effective piece of writing. This study has attempted to explain the types and the most frequent type of errors in writing mechanics found in essays produced by the second semester students of English Department of Universitas Airlangga year 2018/2019. Steps of Error Analysis explained in Gass and Selinker (2008) and the classification of errors by Dulay, Burt, and Krashen (1982) were adopted in this study. The data were collected from 51 typed essays of division and classification written by the semester-two students. The study found in the essays 686 errors in three writing mechanics: punctuation (368), capitalization (291) and spelling (27). The errors belong to four types: addition (271), omission (269), misformation (139), and misordering (7). The two categories combined, the most frequent errors were in the addition of capitalization (211), followed by the omission of commas (160). The findings indicate that capitalization and punctuation become a writing problem for many student participants of this study. Therefore, the problem needs to be dealt with as writing mechanics help make the message in writing conveyed more clearly.Â Keywords: Error Analysis, essays, types of error, writing mechanics